Pengaruh Model Problem Based Learning terhadap Kemampuan Berpikir Kreatif Materi Persamaan Linear - Kauno, Wina Trisva; Susanta, Agus; Hanifah, Hanifah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
ABSTRACT This study aims to determine the effect of problem-based learning on students' creative thinking skills in understanding linear equations. The method used is quantitative research with an experimental approach and descriptive analysis. The population consists of all seventh-grade students at SMPN 17 Bengkulu Utara, with a sample divided into two groups: VIIA as the experimental group with 22 students and VIIB as the control group with 23 students. Data analysis was conducted using SPSS 22, including normality tests, homogeneity tests, and t-tests. The results show a significant difference between the experimental and control groups, with a significance level (sig. (2-tailed)) of 0.000 < 0.05. Therefore, the alternative hypothesis (H₁) is accepted. After implementing problem-based learning, students in the experimental group demonstrated better creative thinking skills than those in the control group. In conclusion, problem-based learning positively influences students' creative thinking skills in understanding linear equations. Keywords: Descriptive analysis, Linear equations, Problem-based learning, SPSS, T-test